Pengaruh Pola Konsumsi Suplemen Zat Besi (Fe) terhadap Risiko Anemia Pada Ibu Hamil di BPM Aida Nospita Desa Manunggal Kecamatan Labuhan Deli Kabupaten Deli Serdang Provinsi Sumatera Utara Tahun 2025 - Parningotan Simanjuntak; Sri Rezeki; Tasya Lamtiur Simanjuntak; Dea Agustina (Detector: Jurnal Inovasi Riset Ilmu Kesehatan, 2025)
Anemia is one of the most common health problems among pregnant women and remains a major challenge in midwifery services. Anemia in pregnancy is primarily caused by iron deficiency, which leads to decreased hemoglobin levels and poses a risk of impaired fetal growth as well as an increased likelihood of delivery complications. Anemia in pregnant women is also one of the contributing factors to the high maternal and neonatal mortality rates (Ministry of Health of the Republic of Indonesia, 2022). This study aimed to determine the effect of iron (Fe) supplement consumption patterns on the risk of anemia among pregnant women at BPM Aida Nospita, Manunggal Village, Labuhan Deli Subdistrict, Deli Serdang Regency, North Sumatra Province, in 2025. This research employed a quantitative design with a descriptive correlational approach. The population of this study comprised all pregnant women attending BPM Aida Nospita in Manunggal Village, Labuhan Deli Subdistrict, Deli Serdang Regency, North Sumatra Province, totaling 45 participants. The results of the analysis indicated a significant relationship between the pattern of iron (Fe) supplement consumption and the risk of anemia in pregnant women (p = 0.000).